Obesity, comorbidities, and treatment selection in Black and White women with early breast cancer. Issue 6 (7th December 2020) - Nyrop, Kirsten A.; Damone, Emily M.; Deal, Allison M.; Carey, Lisa A.; Lorentsen, Michael; Shachar, Shlomit S.; Williams, Grant W.; Brenizer, Addison (Tucker); Wheless, Amy; Muss, Hyman B.
Abstract : Background: This study investigates obesity and comorbidity in Black and White women with early breast cancer (stages I‐III) and their potential impact on treatment decisions for patients with hormone receptor–positive (HR+)/human epidermal growth factor receptor 2–negative (HER2–) tumors. Methods: In this retrospective chart review, comparisons of frequencies for Black and White patients were calculated with the Fisher exact test. Log binomial regression was used to estimate prevalence ratios (PRs) with 95% confidence intervals for total and individual comorbidities, and multivariable modeling was used to estimate PRs adjusted for age and body mass index (BMI). Results: In a sample of 548 patients, 26% were Black, and 74% were White. Sixty‐two percent of Black patients and 32% of White patients were obese (BMI ≥ 30 kg/m 2 ; P < .0001). Seventy‐five percent of Black patients and 87% of White patients had HR+ tumors ( P = .001). Significant intergroup differences were seen for 2 or more total comorbidities (62% of Blacks vs 47% of Whites; P = .001), 2 or more obesity‐related comorbidities (33% vs 10%; P < .0001), hypertension (60% vs 32%; P < .0001), diabetes mellitus (23% vs 6%; P < .0001), hypercholesterolemia or hyperlipidemia (28% vs 18%; P = .02), and hypothyroidism (4% vs 11%; P = .012). In women with HR+/HER2– tumors, there were no intergroup differences in treatment decisions regarding the type of surgery, chemotherapy regimen, radiation, or endocrine treatment despite significant differences in the prevalence of obesity and comorbidities. Conclusions: This study documents significant disparities between Black and White women with early breast cancer with regard to high rates of obesity, overall comorbidities, and obesity‐related comorbidities, and it highlights the prevalence of competing risks that may complicate outcomes in breast cancer. Abstract : This study documents significant disparities between Black and White women with early breast cancer with respect to high rates of obesity as well as overall comorbidities and obesity‐related comorbidities—many of which are independent of age and obesity itself—and it highlights the prevalence of competing risks that may complicate outcomes in breast cancer. Patients need to be counseled that their long‐term overall health and survival depend as much on the effective management of their comorbidities as they do on the successful completion of cancer treatment.